Integrated Assessment of Urban Overheating Impacts on Human Life. Issue 8 (23rd August 2022) - Nazarian, N.; Krayenhoff, E. S.; Bechtel, B.; Hondula, D. M.; Paolini, R.; Vanos, J.; Cheung, T.; Chow, W. T. L.; de Dear, R.; Jay, O.; Lee, J. K. W.; Martilli, A.; et al.
Abstract: Urban overheating, driven by global climate change and urban development, is a major contemporary challenge that substantially impacts urban livability and sustainability. Overheating represents a multifaceted threat to the well‐being, performance, and health of individuals as well as the energy efficiency and economy of cities, and it is influenced by complex interactions between building, city, and global scale climates. In recent decades, extensive discipline‐specific research has characterized urban heat and assessed its implications on human life, including ongoing efforts to bridge neighboring disciplines. The research horizon now encompasses complex problems involving a wide range of disciplines, and therefore comprehensive and integrated assessments are needed that address such interdisciplinarity. Here, our objective is to go beyond a review of existing literature and instead provide a broad overview and integrated assessments of urban overheating, defining holistic pathways for addressing the impacts on human life. We (a) detail the characterization of heat hazards and exposure across different scales and in various disciplines, (b) identify individual sensitivities to urban overheating that increase vulnerability and cause adverse impacts in different populations, (c) elaborate on adaptive capacities that individuals and cities can adopt, (d) document the impacts of urban overheating on health and energy, and (e) discuss frontiers of theoretical and applied urban climatology, built environment design, and governance toward reduction of heat exposure and vulnerability at various scales. The most critical challenges in future research and application are identified, targeting both the gaps and the need for greater integration in overheating assessments. Plain Language Summary: Many major cities are faced with the compounding effects of climate change and rapid urbanization. One of the main challenges that result is urban overheating, which leads to negative impacts on human life (deteriorating health, productivity, and well‐being) and urban energy systems. Heat exposure in cities, however, is only the trigger and there are other factors that influence impacts. Urban heat vulnerability exists when sensitive people and infrastructure are exposed to extreme heat, and negative impacts ensue if there is a lack of capacity to respond and adapt. Accordingly, to combat overheating challenges, it is critical that multidisciplinary solutions are integrated to mitigate exposure, reduce sensitivity, and increase adaptive capacities. This paper provides an integrated assessment of urban overheating literature, defining pathways for addressing the impacts on human life. We review the state‐of‐the‐art methods used to quantify heat hazards and exposure, detail the sensitivity of people and infrastructure to overheating, and elaborate on the adaptive capacities that individuals and cities can undertake in response. We provide recommendations for both researchers and policymakers that will minimize overheating impacts. These recommendations range from modifications to urban and building design to engaging citizens and informing urban overheating governance. Key Points: Urban overheating is the exceedance of locally‐defined thermal thresholds that lead to negative impacts on people and urban systems Exposure to heat hazards compounded with sensitivity and reduced adaptive capacity of people and urban systems lead to increased risk levels Research and application should provide integrated solutions to mitigate exposure, reduce sensitivity, and increase adaptive capacities